Sistem Pembalajaran Berbasis Teknologi Pada Mata Kuliah Akuntansi Manajemen Untuk Meningkatkan Efektivitas Dan Efisiensi Pembelajaran: Technology Based Learning System in Management Accounting Course to Enhance Learning Effectiveness and Efficiency - Husen, Sri Rahayu; Apriana, Ririn (Jurnal Ilmiah Produktif, 2025)
The development of information technology has driven a paradigm shift in the world of education, including in higher education learning. This study aims to examine the implementation of technology-based learning systems, specifically the use of Learning Management Systems (LMS) and interactive media, in enhancing the effectiveness and efficiency of learning in the Management Accounting course. The research method used is quantitative with a quasi-experimental design. The research sample consists of 60 management program students, divided into two groups: the experimental group, which uses technology-based learning, and the control group, which follows the conventional method. Data collection is conducted through pre-test, post-test, questionnaires, observation, and interviews. Data analysis is performed using t-test (independent sample t-test) and descriptive analysis. This study concludes that technology-based learning systems not only improve effectiveness in achieving learning outcomes but also enhance efficiency in the use of time and resources.